Mechanism of action of the novel nickel (II) complex in simultaneous reactivation of the apoptotic signaling networks against human colon cancer cells - Nima eSamie (Frontiers Media S.A., 2016)
The aim of this study was to evaluate the cytotoxic potential of a novel nickel (II) complex (NTC) against WiDr and HT-29 human colon cancer cells by determining the IC50 using the standard MTT assay. The NTC displayed a strong suppressive effect on colon cancer cells with an IC50 value of 6.07 ± 0.22 µM and 6.26 ± 0.13 µM against WiDr and HT-29 respectively, after 24 h of treatment. Substantial reduction in the mitochondrial membrane potential and increase in the release of cytochrome c from the mitochondria directed the induction of the intrinsic apoptosis pathway by the NTC. Activation of this pathway was further evidenced by significant activation of caspase 3/7 and 9. The NTC was also shown to activate the extrinsic pathway of apoptosis via activation of caspase-8 which is linked to the suppression of NF-ƙB translocation to the nucleus. Cell cycle arrest in the G1 phase was confirmed by flow cytometry and up-regulation of glutathione reductase expression was quantified by qPCR. Results of the current work indicates that NTC possess a potent cancer cell abolishing activity by simultaneous induction of intrinsic and extrinsic pathways of apoptosis in colon cancer cell lines.